Платоновские контексты: Павел Филонов и учение Николая Федорова - Geller, Leonid (Wiener Slawistischer Almanach, 2022)
Proposing to explore the parallel between the creative visions and practice of the painter Pavel Filonov and the writer Andrej Platonov, the paper develops the postulates put forward in an author‘s prior work. The features that are common to both artists appear on three levels: poetics of the futuristic shift (sdvig); primitivist vision; proximity to the philosophical oeuvre by Nikolaj Fedorov.